The development, validation and application of a primary school science curriculum implementation questionnaire. - Lewthwaite, Brian (Curtin University, 2001)
This study focuses on the identification of the broad and complex factors influencing primary science program delivery within the New Zealand context. The study is divided into two phases. In the first phase, the factors influencing science program delivery are identified through (1) a questionnaire survey of 122 teachers in the Central Districts of New Zealand; (2) a questionnaire survey of 155 pre-service teachers at a New Zealand College of Education; (3) a case study of a large intermediate school in the Central Districts; and (4) a review of the research literature pertaining to curriculum, in particular primary science, delivery. Factors influencing science program delivery are identified as being both personal (intrinsic) and environmental (extrinsic). Intrinsic factors identified include teacher professional self-efficacy; interest and motivation; and multidimensional aspects of knowledge. Extrinsic factors influencing science program delivery include multidimensional aspects of time availability and resource adequacy; the availability and adequacy of professional support and leadership; and the priority placed on science as a curriculum area by the school, especially by the administration. The second phase of the study built on this initial phase by focusing on the development of an instrument, the Science Curriculum Implementation Questionnaire, which assists schools in identifying factors influencing science program delivery. The development of the SC1Q initially involved the use of a Focus Group to identify and prioritise items to include in the instrument. Statistical validation involved trialling of the SCIQ amongst 293 teachers representing 43 schools in the Central Districts of New Zealand. Using statistical procedures involving ANOVA, alpha reliability and discriminant validity, a seven-scale, 49-item instrument was developed. On the basis of the strong overlap amongst the intrinsic factors influencing science delivery, a further, shorter five scale, 35-item instrument was developed. The seven-scale SCIQ was further applied at the case study school. Quantitative data collected from the application of the instrument confirmed that several psychosocial and physical aspects of Intermediate School identified in the case study are influencing science program delivery. Implications of this study and the practical applications of the Science Curriculum Implementation Questionnaire are also presented in the context of primary science delivery both within New Zealand and internationally.